Transformasi Strategi Disiplin Guru: Dari Hukuman ke Pendekatan Edukatif dalam Membentuk Kedisiplinan - Nabila Ayu Mulyadi; Amanda Mardillah; Ikmawati Ikmawati; Achmad Muhtadin (Jurnal Motivasi Pendidikan dan Bahasa, 2026)
This study aims to examine the transformation of teachers’ discipline strategies from a punishment-based approach to an educational approach in fostering student discipline. The persistent issues of student discipline, such as low compliance with rules and lack of learning responsibility, indicate the need for more effective disciplinary strategies. This study employs a literature review method by analyzing various relevant scientific articles related to discipline strategies, the implementation of rewards and punishments, and positive discipline approaches in the school environment. The findings reveal a shift in discipline strategies from those emphasizing control through punishment to more educational and humanistic approaches. This approach focuses on the habituation of positive behavior, empathetic communication, and the provision of rewards to strengthen students’ motivation. However, punishment still plays a role as a learning tool when applied fairly, consistently, and proportionally. In addition, the success of fostering student discipline is influenced by teachers’ role modeling, firmness in enforcing rules, and a supportive school environment. This transformation indicates that teachers act not only as rule enforcers but also as facilitators who encourage the development of students’ internal awareness and responsibility. Therefore, the implementation of balanced and sustainable discipline strategies is essential to support an effective learning process.